The adolescent brain at risk for substance use disorders: a review of functional MRI research on motor response inhibition. (February 2017) - Koyama, Maki S; Parvaz, Muhammad A; Goldstein, Rita Z
Highlights: Family history of substance use disorders (SUDs) and ADHD are risk factors for SUD. Neural correlates of motor response inhibition in youth at risk for developing SUDs. No common neural alteration in youth with family history of SUDs and youth with ADHD. Distinct neural alterations specific to each at-risk group. Blunted frontal activity may predict later SUDs, irrespective of SUD family history. Abstract : Youth with family history (FH+) of substance use disorders (SUDs) are at increased risk for developing SUDs. Similarly, childhood attention deficit hyperactivity disorder (ADHD) is considered to be a risk factor for developing SUDs. Recent research has suggested a close association between SUDs and impaired inhibitory control. As such, it is crucial to examine common and distinct neural alterations associated with inhibitory control in these at-risk groups, particularly prior to the initiation of heavy substance use. This paper reviews the functional magnetic resonance imaging (fMRI) literature of inhibitory control in these two at-risk youth populations (FH+ and ADHD), specifically considering studies that used motor response inhibition tasks (Go/No-Go or Stop Signal). Across the selected fMRI studies, we discovered no common alteration in the at-risk groups, but found neural alterations specific to each at-risk group. In FH+ youth and youth who transitioned into heavy substance use, blunted activation in the lateral part of the frontal pole (FP-lat) was most reliably observed. Importantly, longitudinal studies indicate that the blunted FP-lat activation may predict later SUDs, irrespective of the presence of FH+. In regards to ADHD, blunted activation was observed in the right dorsal anterior cingulate cortex (dACC) and left caudate. Of note, similar blunted dACC activation was also reported by one FH+ study, and thus, we cannot preclude a possibility that the right dACC activity may be a potential common alteration in both at-risk groups, particularly given a limited number of FH+ studies in the current review. Research challenges remain, and large-scale, longitudinal efforts will help determine the neurobiological markers predictive of SUDs among at-risk adolescents, including those with FH+, as well as those with ADHD and other psychiatric disorders.